2017
DOI: 10.1080/10245332.2017.1404219
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of oral and dento-maxillofacial manifestation of patients with sickle cell diseases and beta thalassemia major

Abstract: Finally, the study gives an insight into the various oral and dento-maxillofacial manifestations of SCD and BTM and also reveals an association that exists between the oral and dento-maxillofacial manifestations and systemic health in these patients, thus stressing the importance of the concise and periodic examination of these individuals to perform appropriate preventive dental and periodontal care, and the facilitation of the management of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
2
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 20 publications
2
29
2
4
Order By: Relevance
“…According to our search strategy, we comprehensively retrieved and identified 78 and 41 articles from PubMed and Embase, respectively. We reviewed 13 full-text articles; however, the investigators of one of the 4 studies did not provide available data [11,16,29,30]. Although we sent emails to contact the corresponding authors of these studies, we received no reply.…”
Section: Analysis Of Subgroupsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to our search strategy, we comprehensively retrieved and identified 78 and 41 articles from PubMed and Embase, respectively. We reviewed 13 full-text articles; however, the investigators of one of the 4 studies did not provide available data [11,16,29,30]. Although we sent emails to contact the corresponding authors of these studies, we received no reply.…”
Section: Analysis Of Subgroupsmentioning
confidence: 99%
“…Ultimately, we included a total of 9 studies within 8 publications featuring a comparison group included in the systematic review and in the meta-analysis [9,15,16,22,23,32-34]. Table 1 summarizes the main characteristics of the included studies [9,15,16,22,23,[32][33][34]. The publication year ranged from 2002 to 2018.…”
Section: Analysis Of Subgroupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients with thalassemia major are found to have significantly higher DMFT in comparison to those with thalassemia intermedia [31]. Of note, DMFT index has been reported to be higher in thalassemia patients than in SCD [29,32]. It has been suggested that this increased caries experience in thalassemia might be due to lower concentrations of IgA in saliva, which could allow increased microbial proliferation [23].…”
Section: Anemia and Oral Healthmentioning
confidence: 99%
“…Patients with thalassemia were shown to have increased levels of several inflammatory markers in gingival crevicular fluid and in saliva, such as IL-6, IL-8, matrix metalloproteinase (MMP)-8, MMP-9, and tissue inhibitor of metalloproteinase (TIMP)-1, compared with a systemically healthy group suggesting an exacerbation of the local immune response in these patients, which could affect the periodontal condition [48,50]. Whether there is a difference in periodontal status between thalassemia and SCD is not clear, though it has been shown that thalassemia patients have more missing teeth than SCD patients [32].…”
Section: Anemia and Oral Healthmentioning
confidence: 99%